KHALAYAK MAYA DALAM MEDIA ONLINE : Studi Reception Analysis tentang Interaktivitas pada Teks Suara Surabaya.net - Hadi, Ido Prijana (Institute of Research and Community Outreach - Petra Christian University, 2007)
Internet as a global computer-network that combine image, motion-pictures, text, and audio-visual. Internet has differentiated itself from earlier media types through what is called as interactivity. Interactivity is an uniqueness of internet media particularly in terms of its contents, such as feedback mechanism through email (electronic mail), online chat-room or live interviews. Its information is easily searchable, updated at any time, and can be linked to other sites. The research was carried out to find out how user reception on interactivity in online media on the site of Suara Surabaya.net. And how to access subjective meanings that they have created based on their understanding on online media so far. The research is also interested in looking into user reception on information and communication technology based on its relevance with the selected theme namely discourse on global media in web site of Radio Suara Surabaya. Interactivity value of Suara Surabaya.net was obtained by users through hyperlinks, book-marking the site of Suara Surabaya.net and mechanism of feedback that provide users with opportunities to get in touch with editorial staff, as well as other users. Therefore, that can respond to one another by means of users to users namely individuals interact with other individuals in online discussion, more de-massified in nature - personal (nullifying things that are massed in nature); Whereas response of users to documents are individuals access rubrics of news, article, archive, searching, photograph, and so on. News can be framed and regulated into any format wanted by users, not waiting anymore for schedules of media publishing time (publishing time periodicity). Users are unhampered in accessing the required information. Meanwhile users to computers (online transaction) is interaction with users to the computer itself.